2015
DOI: 10.1111/peps.12123
|View full text |Cite
|
Sign up to set email alerts
|

Does Coaching Matter? A Multilevel Model Linking Managerial Coaching Skill and Frequency to Sales Goal Attainment

Abstract: Managerial coaching is a process of feedback provision, behavioral modeling, and goal setting with subordinates to improve their performance and address their personal challenges. Despite the popularity of coaching as a management practice, the impact of coaching on objective measures of performance remains unclear. To this end, we tested a multilevel model linking managerial coaching frequency and skill to the sales goal attainment of 1,246 sales representatives in 136 teams within a pharmaceuticals organizat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
99
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(100 citation statements)
references
References 77 publications
1
99
0
Order By: Relevance
“…Planning and goal setting refers to the ability to support employees in establishing individual development goals that are valued by them, and ensure that they complete the agreed-upon action steps (Grant and Cavanagh, 2007b). Previous research has indicated that leaders as coaches work collaboratively with each employee to set engaging, challenging goals that motivate performance (Dahling et al, 2016). Finally, managing progress requires leaders to monitor, re-define, and evaluate employee action plans and performance, and manage both responsibilities in the process (Grant, 2003;Grant and Cavanagh, 2007b).…”
Section: Progress and Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Planning and goal setting refers to the ability to support employees in establishing individual development goals that are valued by them, and ensure that they complete the agreed-upon action steps (Grant and Cavanagh, 2007b). Previous research has indicated that leaders as coaches work collaboratively with each employee to set engaging, challenging goals that motivate performance (Dahling et al, 2016). Finally, managing progress requires leaders to monitor, re-define, and evaluate employee action plans and performance, and manage both responsibilities in the process (Grant, 2003;Grant and Cavanagh, 2007b).…”
Section: Progress and Resultsmentioning
confidence: 99%
“…First, this is the first empirical study to evaluate and confirm the positive effects of a coachingbased leadership intervention on increasing the levels of the leaders' coaching skills, PsyCap, work engagement, and in-role and extra-role performance. Since the coaching-based leadership term remains undertheorized (Berg and Karlsen, 2016), and its value and meaning within the organizational context have not been sufficiently captured (Dahling et al, 2016), findings of the current study can notable contribute to research on the benefits of this relatively new style of leadership. Additionally, identifying the attributes and outcomes that are most frequently associated with coaching-based leadership may allow for insight into the concept and further theory development (Cox et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…It commences with agreeing on the goals for the programme (Rider, 2002). Numerous authors emphasise the role of goal-setting in coaching (Smither, 2011;Crane, 2001;Dahling et al, 2016). Alexander and Renshaw (2005) stress the importance of setting goals to give purpose and direction to the coaching session and to prevent it from becoming "a meandering natter".…”
Section: Setting Goalsmentioning
confidence: 99%
“…The role of feedback is emphasised by many specialists (Grant, 2013;Dahling et al 2016;Wheeler, 2011). Feedback explains why behaviours are effective or ineffective, quotes specific examples, allows the person receiving feedback to comment, provides alternative positive behaviours, maintains esteem of those involved (Latham & Marchbank, 1994).…”
Section: Coaching Process and Its Influence On Employees' Competenciementioning
confidence: 99%
See 1 more Smart Citation